1997
DOI: 10.1523/jneurosci.17-02-00667.1997
|View full text |Cite
|
Sign up to set email alerts
|

Resetting the Biological Clock: Mediation of Nocturnal CREB Phosphorylation via Light, Glutamate, and Nitric Oxide

Abstract: Synchronization between the environmental lighting cycle and the biological clock in the suprachiasmatic nucleus (SCN) is correlated with phosphorylation of the Ca 2ϩ /cAMP response element binding protein (CREB) at the transcriptional activating site Ser 133 . Mechanisms mediating the formation of phospho-CREB (P-CREB) and their relation to clock resetting are unknown. To address these issues, we probed the signaling pathway between light and P-CREB. Nocturnal light rapidly and transiently induced P-CREB-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
159
0
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(169 citation statements)
references
References 80 publications
4
159
0
6
Order By: Relevance
“…Glutamate (1mM) applied for 10 min at ZT 23 induced robust phase advances of about 3 h (Fig. 5), consistent with previously reported results in rats (Ding et al, 1994;Ding et al, 1997;Ding et al, 1998). As seen with glutamate-induced phase delays, co-application of 20 mM ethanol completely blocked glutamate-induced phase advances, while having no effect on the phase of neuronal activity when applied alone.…”
Section: Ethanol Inhibition Of Glutamate-induced Phase Advances Is Insupporting
confidence: 91%
See 1 more Smart Citation
“…Glutamate (1mM) applied for 10 min at ZT 23 induced robust phase advances of about 3 h (Fig. 5), consistent with previously reported results in rats (Ding et al, 1994;Ding et al, 1997;Ding et al, 1998). As seen with glutamate-induced phase delays, co-application of 20 mM ethanol completely blocked glutamate-induced phase advances, while having no effect on the phase of neuronal activity when applied alone.…”
Section: Ethanol Inhibition Of Glutamate-induced Phase Advances Is Insupporting
confidence: 91%
“…Previous work has shown that glutamate-induced phase shifts require generation of nitric oxide (NO) (Ding et al, 1994;Ding et al, 1997), and in vitro application of glutamate to SCN slices induces NO production that is inhibited by AP5, K252a and the nitric oxide synthase (NOS) antagonist, L-NAME (R.A. Prosser and Y. Lee, unpublished results). Here we tested whether DPAT-induced phase shifts are enhanced by blocking NOS activity with L-NAME.…”
Section: Blocking Nitric Oxide Generation Enhances Serotonergic Phasementioning
confidence: 99%
“…[20][21][22][23] Alterations in sGC expression and function in the brain in cirrhotic patients, therefore, could relate to the neuropsychiatric symptoms such as sleep disturbances and memory …”
Section: Discussionmentioning
confidence: 99%
“…Light administered in the dark phase is thought to elicit glutamate release in the synapses of the RHT, because glutamate can mimic the effects of light. Glutamate activates ionotropic glutamate receptors in the SCN, which trigger influx of Ca 2+ (Ding et al, 1994(Ding et al, , 1997Schurov et al, 1999). This leads to the activation of several signal transduction pathways (reviewed in Hirota & Fukada, 2004) and evokes modification of chromatin (Crosio et al, 2000) and clock proteins (Myers et al, 1996) plus the activation of immediate early genes, such as c-Fos (Kornhauser et al, 1990) and the clock genes Per1 and Per2 (Albrecht et al, 1997;Shearman et al, 1997;Shigeyoshi et al 1997;Yan & Silver, 2002).…”
Section: Introductionmentioning
confidence: 99%